GALERI METHACRAFT KANDANGAN - Rahmah, Dessy Aulia; Mentayani, Ira (UNIVERSITAS LAMBUNG MANGKURAT, 2020)
Kandangan Methacraft Gallery is a place used by craftsmen to carry out their craft activities from the processing, marketing, and selling handicrafts of Hulu Sungai Selatan Regency. The purpose of this design is an area that can increase people's interest to come and become a place for those who want to work and develop their potential. This gallery uses a storyboard as a method and sequence of movement as concept programmatic that will provide a space experience to get to know in crafts more deeply. Storyboarding methods will be applied by borrowing the comic system, not the comic form but how a comic works so that it can tell stories.